SIMULATION OF STATIC AND DYNAMIC LOSSES IN MOSFET KEYS - V. P. Babenko; V. K. Bityukov; V. V. Kuznetsov; D. S. Simachkov (Российский технологический журнал)
Issues of modeling of losses in MOSFET keys from the Electronics Workbench (EWB) program library as well as optimization of the power key operation mode are considered. A number of important facts have been obtained by using the EWB program of circuit simulation, which should be taken into account when designing power electronics devices and secondary power sources for radioelectronic facilities, in particular. It is shown that the power of static losses depends on the resistance of the open transistor channel, the current flowing through the transistor, duty cycle, and it does not depend on the gate current. While the power of dynamic losses at the time of switching the transistor on depends on the gate current, it decreases with the increasing current. When a gate current (driver) is more than 0.6 A, the reduction of loss is insignificant, and it is best to choose a driver with output currents of more than 0.6 A. However, this is true only for the investigated IRF1010N transistor. In the schemes of building the MOSFET keys on other transistors, the best output current of the driver may differ. The power of dynamic losses when turning the transistor off does not depend on the gate current. However, this is true only for this scheme, because the discharge of the gate capacitance occurs through a resistor with a fixed value for the key resistance. Usually the output stage in the control circuit is executed in a push-pull circuit and has the same output resistance for the incoming and outgoing output current of the driver, the physical processes of switching on and switching off are practically identical, and so the quantitative results can be close. The simulation of the MOSFET key in the EWB program provides adequate results in determining the parameters of the power transistors, which are in agreement with the data given in the Datasheet. This allows simulating the key losses and minimizing them at any load.